Learnings from a Pilot Citizen Panel Research project with minoritized groups in the UK - Garbovan, Lidis; Flaig, Robin (International Journal of Population Data Science, 2025)
Objective The Citizen Panel is a pilot research project embedding public feedback and perceptions into data access decision-making. The project involves the public in decisions around the acceptance and suitability of data use, assessing the scope and benefit of research questions and creating a learning feedback loop for decision-making. Methods The Citizen Panel was recruited from both Longitudinal Population Studies (LPS) and public members traditionally not included in longitudinal research. The Panel met online three times from October to December 2024. Materials were provided in advance to explain the access process. The meetings combined presentations to the panel where they could discuss and ask questions about the data access and decision-making process for research using LPS data linked to administrative data. Their final meeting was a full-day Workshop on 31 Jan 2025 in a hybrid format, in person and online. The Workshop focussed on facilitated group discussions, reflections and activities. Results The Panel members reflected on the online meetings in 2024, reviewed the data access process, and made recommendations for involving public and minoritized groups in the decision-making process. The Panel recommended embedding Equality, Diversity and Inclusion as a toolkit in the data access process to help assessing public good in research applications. The Panel also made recommendations for co-producing a 2nd stage of the project in 2025 and sharing outputs to wider audiences in creative and accessible formats. The Panel is strongly interested in a tangible outcome of the project. The Citizen Panel project is aimed at inclusion of seldom heard groups in longitudinal research and the preliminary results show that the Citizen Panel was delivered in a way that the panel members felt valued. Conclusion The first round of the pilot Citizen Panel provided a set of recommendations that will be reviewed and where appropriate incorporated into the access process and fed back to the Panel. The learnings will help shaping the second round of the project, in dialogue with the Panel Members.